Training Strategies In Lic: The Impact of Training Strategies on Employee Performance in LIC (Journal of Advances and Scholarly Researches in Allied Education, 2012)
HumanResource is the most vital resources for the reason that is the only resourcewhich has got brain. Even the computer brain which has been developed has humanbrain behind it. Development is a systematic process of learning and growth bywhich managerial personnel gain and apply knowledge, skills, attitudes andinsight to manage the work in their organization effectively and efficiently.Present study emphasis the attitude of employees towards Training andDevelopment programmes affect their performance. To achieve this objectiveprimary data is collected with the help of questionnaires as well as Interviewmethod. The questionnaires were filled up by 100 employees. In this researchpaper the hypothesis taken up for conducting the research was true and trainingand development programmes adopted by LIC help in improving employee’sperformance.